A MULTIDIMENSIONAL STUDY ON THE COGNITION OF SOCIAL SITUATIONS - HIROOKA, SHUICHI (Jikken shakai shinrigaku kenkyū, 1985)
The purposes of the present study are to explore the cognitive structure of social situations and to examine sex differences in them. One hundred and sixteen undergraduates (58 males and 58 females) served as subjects. The subjects were asked to classify thirty social situations into five to nine categories according to their similarities. Then, they were asked to rate social situations on twelve situation rating scales. Major findings obtained are as follows: 1. The dimensions, which were extracted from rating situations, were (1) intimacy, (2) task-orientation, and (3) anxiety. 2. Sex differences in the relative salience of the dimensions in ratings, as presented by the INDSCAL weights, were found. Specifically, males gave greater weight to dimension (2), while females gave greater weight to dimension (3). 3. A fairly high degree of correspondence was found among the cognitive structures obtained by ratings and similarity judgments.